2016
DOI: 10.1016/j.jcf.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary infection–colonization patterns in Spanish cystic fibrosis patients: Results from a national multicenter study

Abstract: The representative subset of the Spanish CF-population which has been clinically, demographically and microbiologically characterized will serve as a reference for future CF studies in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…SXT is the antibiotic of choice for treating S. maltophilia infections, although in recent years, increasing rates of resistance, ranging from 16% to 45%, were reported, especially in CF patients [9,35,36]. Considering available clinical breakpoints, our results confirmed SXT is the most active compound against all the strains tested.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…SXT is the antibiotic of choice for treating S. maltophilia infections, although in recent years, increasing rates of resistance, ranging from 16% to 45%, were reported, especially in CF patients [9,35,36]. Considering available clinical breakpoints, our results confirmed SXT is the most active compound against all the strains tested.…”
Section: Discussionsupporting
confidence: 70%
“…We found that CF strains were significantly more resistant to piperacillin-tazobactam than non-CF strains (90% versus 53.3%, respectively). This finding might be the consequence of the airways' concomitant colonization/infection by both S. maltophilia and P. aeruginosa observed in CF patients [35,40,41]. Consequently, the higher use of this antipseudomonal beta-lactam/beta-lactamase inhibitor combination in CF patients might have exerted a positive antibiotic pressure associated with higher levels of resistance.…”
Section: Discussionmentioning
confidence: 95%
“…Cystic fibrosis (CF) patients are regularly colonized by opportunistic microorganisms. In adult patients, Pseudomonas aeruginosa is the main pathogen, but in recent years, other nonfermenting bacteria from different genera, such as Stenotrophomonas, Burkholderia, Achromobacter, Ralstonia, and Pandoraea, are increasingly being isolated [1][2][3]. This could be potentially due to the aggressive antimicrobial therapy used against P. aeruginosa, to the apparition of new techniques for the bacterial identification and improvement in life expectancy for people with CF [4].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms of P. aeruginosa are particularly relevant in chronic pulmonary infections in CF patients, where eradication is very difficult. About 54% of CF patients under the age of 18 years are colonized by this microorganism, while the percentage rises to 80% in adults (9).…”
Section: Discussionmentioning
confidence: 99%